Francoféminisme en Tunisie : pratiques langagières et enjeux institutionnels - Mariem Guellouz; Sélima Kebaïli (Glad!)
This article presents an analysis of the links between French-speaking world and feminism in the Arab world. Feminism in the Arab world, while linked from its beginnings to colonial, social and political struggles, has also been influenced by the various institutional choices made by post-independence national elites in Tunisia. In particular, the history of women's rights has been marked by the various state measures aimed at making the country a pillar of the institutional Francophonie, making the use of the French language inseparable from feminism. Based on historical archives and ethnographic fieldwork in Tunisia, the article analyses language ideologies that articulate the practice of the French language and modernity as well as the processes that has participated to shape the institutional and activist feminist field in Tunisia. and proposes the term francofeminism to characterize this process.